2010
DOI: 10.1088/1468-6996/11/1/014109
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nanoassemblies of block copolymers for future cancer therapy

Abstract: Nanoassemblies from amphiphilic block copolymers are promising nanomedicine platforms for cancer diagnosis and therapy due to their relatively small size, high loading capacity of drugs, controlled drug release, in vivo stability and prolonged blood circulation. Recent clinical trials with self-assembled polymeric micelles incorporating anticancer drugs have shown improved antitumor activity and decreased side effects encouraging the further development of nanoassemblies for drug delivery. This review summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…Additionally, Polymer Therapeutics of other classes, such as polymeric micelles and polyelectrolyte complexes as non‐viral vectors are in advanced clinical trials. In these latter families, Prof. Kataoka's research group is one of the major references …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Polymer Therapeutics of other classes, such as polymeric micelles and polyelectrolyte complexes as non‐viral vectors are in advanced clinical trials. In these latter families, Prof. Kataoka's research group is one of the major references …”
Section: Introductionmentioning
confidence: 99%
“…In addition to study crosslinking effect on the PDT efficiency, these choices enabled us rst to examine the molecular weight effect of the polymer without changing the self-assembly morphology (PEO-PCL 2000-2800 vs. 5000-4000) and secondly to examine elongated systems which were suggested in the literature as more efficient than spherical ones. [58][59][60] These polymers were functionalized by graing an acrylate group, through reaction between hydroxyl end groups and acryloyl chloride, at the end of different poly(ethyleneoxide-b-3-caprolactone) copolymers (Scheme 1A) following already published procedures. 14,[61][62][63] Functionalization ratio was determined by 1 H NMR (Fig.…”
Section: Crosslinked Polymer Self-assemblies Synthesis and Characterimentioning
confidence: 99%
“…Nanostructures, especially spherical polymeric self‐assemblies and their related aggregates, have recently attracted increased attention because of their huge potential to be used in medical applications, for examples as imaging agents or as carriers of drugs . Based on the phenomenon known as the enhanced permeability and retention (EPR) effect, via which nanometer‐size polymeric self‐assemblies accumulate passively and specifically in tumor tissues, research related to tumor diagnosis and therapy using self‐assemblies has intensified . The control of the size of self‐assemblies is one of the most important topics in this field, because it was recently reported that the size of polyion complex hollow vesicles (PICsomes) significantly affects their in vivo kinetics and tumor specificity for drug delivery .…”
Section: Introductionmentioning
confidence: 99%